1993
DOI: 10.1213/00000539-199301000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Function and Adenosine Triphosphate Metabolism Following Myocardial Ischemia Induced in the Presence of Volatile Anesthetics

Abstract: Using a normothermic isolated working rabbit heart model, experiments were performed to determine whether exposure to halothane or isoflurane prior to ischemia improved postischemic recovery of myocardial function and the preservation of myocardial high energy phosphates. After 30 min of Langendorff perfusion, hearts were perfused for 30 min in the working mode. Three groups were studied: 1) the blank undergoing no pretreatment during an additional 15 min of working mode; 2) hearts exposed to 1.5% halothane; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…In these experiments, volatile anesthetics were delivered before ischemia, during ischemia, and during the reperfusion period. In contrast to the above studies, Mattheussen et al [9] showed that exposure to halothane or isoflurane only prior to ischemia had no effect on functional and metabolic indices of recovery after myocardial stunning. In addition, Belo et al [10] demonstrated that subsequent administration of halothane or isoflurane after reperfusion did not improve contractile function in stunned myocardium.…”
Section: Introductionmentioning
confidence: 85%
“…In these experiments, volatile anesthetics were delivered before ischemia, during ischemia, and during the reperfusion period. In contrast to the above studies, Mattheussen et al [9] showed that exposure to halothane or isoflurane only prior to ischemia had no effect on functional and metabolic indices of recovery after myocardial stunning. In addition, Belo et al [10] demonstrated that subsequent administration of halothane or isoflurane after reperfusion did not improve contractile function in stunned myocardium.…”
Section: Introductionmentioning
confidence: 85%
“…Coetzee et al 7 suggested that the beneficial effects of inhalation anesthetics after cardioplegic arrest might be related to the prevention of the reperfusion injury and could not be ascribed to depression of global myocardial contractile function. Mattheussen et al 19 have assessed the effect of inhalation anesthetics on myocardial metabolism using the ischemic working heart preparation. Although they employed the same experimental model as we did, inhalation anesthetics were administered only during the pre-ischemic period and they did not affect myocardial high energy phosphates at the end of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile anaesthetics to various degrees have been shown to decrease myocardial contractility and myocardial oxygen demand, a property that has been suggested to explain cardioprotection against ischaemia and reperfusion ( Coetzee et al , 1993 ; Mattheussen et al , 1993 ; Schlack et al , 1998 ). However, these anaesthetics were also found to induce cardioprotection via mechanisms that are similar to pathways involved in ischaemic preconditioning ( Cope et al , 1997 ).…”
Section: Anaesthetics As Cardioprotective Agentsmentioning
confidence: 99%